Polish Media System in a Comparative Perspective : Media in Politics, Politics in Media - Dobek-Ostrowska, Boguslawa (2019)
A media system does not exist in a vacuum. It develops and grows within social, political and economic systems. They interact with and influence one another, as well as stimulate each other’s development. The main subject of this work is the dynamically evolving Polish media system, which is under the influence of institutions and external stakeholders. Thanks to this, it is easier to understand that the "crossroads" is not only a problem of the Polish media system, but a global one. For this reason, a comparative perspective is employed. Three chapters help to provide an answer to research questions dedicated to political parallelism and journalistic professionalization. The analysis would be limited and unrepresentative if the book enclosed it with one country's border, omitting the broad global, European and Centro-European context.